2020
DOI: 10.1108/meq-08-2020-0168
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of healthcare solid waste management practices for environmental performance: a study of hospitals in Himachal Pradesh, India

Abstract: PurposeThe day-by-day escalating quantity of healthcare waste (HCW), has made waste handling and management a challenging issue for ensuring environmental quality. Developing nations like India face huge difficulties in handling healthcare solid wastes (HCSW) because of the extra population burden. Hence, the present study seeks to evaluate the role of various stakeholders, under the following four performance areas: “collection and segregation of HCSW,” “storage and transportation of HCSW,” “special measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Digital platform will help to ensure the IT enabled MSWM system and also help in educating the smart city residents about the various initiates taken by the administration (An et al, 2015). The tracking based MSWM supply chain and managing the robust information system will ensure the safe transportation and disposal of the MSW in the smart cities (Thakur et al, 2021;Thakur and Sharma, 2020). The study also identified the strong role of MSW collection network from the public bins installed and community toilets constructed for 100% waste collection and disposal in the smart cities (Thakur, 2021).…”
Section: Empirical Validation Of Tism-based Mswm Framework: Case Stud...mentioning
confidence: 99%
“…Digital platform will help to ensure the IT enabled MSWM system and also help in educating the smart city residents about the various initiates taken by the administration (An et al, 2015). The tracking based MSWM supply chain and managing the robust information system will ensure the safe transportation and disposal of the MSW in the smart cities (Thakur et al, 2021;Thakur and Sharma, 2020). The study also identified the strong role of MSW collection network from the public bins installed and community toilets constructed for 100% waste collection and disposal in the smart cities (Thakur, 2021).…”
Section: Empirical Validation Of Tism-based Mswm Framework: Case Stud...mentioning
confidence: 99%
“…A third one is the international standard (ISO) issued by the International Organization for Standardization, which is considered the most widespread and accepted in the international projects. It is the system of the international standard ISO 14001 series (Thakur and Sharma, 2021) .…”
Section: Development Of Theory and Hypothesismentioning
confidence: 99%
“…Empirical evidence from China shows that greenhouse gas emissions, such as carbon, cause higher health issues (Farooq et al., 2019). Health issues caused by environmental pollution are also evident in other developing countries, such as India (Thakur & Sharma, 2021).…”
Section: Theoretical Analysis and Hypothesesmentioning
confidence: 99%